Trades access common core. Line A, Safe Work Practices, Competency A-5, Describe fire safety B.C. - Lidstone, Rod; Camosun College; British Columbia. Ministry of Technolgy, Innovation and Citizens' Services; BC Open Textbook Project; BCcampus (Ministry of Technology, Innovation and Citizens' Services, 2015)
"As a trades worker you have a responsibility to work safely, and fire prevention is a primary concern. Many of the work tasks you carry out include the application of heat and flame. You should be able to apply fire prevention practices, identify fire causes, and identify and apply fire extinguishing agents to control or extinguish a fire. You are not expected to be an expert firefighter, but you may have to deal with a fire to protect your safety and the safety of others. The following list of lines and competencies was generated with the goal of creating an entry-level trades training resource, while still offering the flexibility for lines to be used as stand-alone books. Line A Books include: A-1 Control Workplace Hazards, A-2 Describe WorkSafeBC Regulations, A-3 Handle Hazardous Materials Safely, A-4 Describe Personal Safety Practices, A-5 Describe Fire Safety."--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
"Copyright Camosun College"--P. 2.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online resource; title from pdf title page (viewed on January 7, 2016).
Keywords: Industrial safety -- Textbooks; Fire prevention -- Textbooks; Electronic books